The potential of bird diversity in the urban landscape for birdwatching in Java, Indonesia - Insan Kurnia; Harnios Arief; Ani Mardiastuti; Rachmad Hermawan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kurnia I, Arief H, Mardiastuti A, Hermawan R. 2021. The potential of bird diversity in the urban landscape for birdwatching in Java, Indonesia. Biodiversitas 22: 1701-1711. Birdwatching is a recreational activity of observing birds in the wild with the naked eye¸ using tools such as telescopes and binoculars, or listening to bird sounds. The observation locations can be either natural landscape or urban landscapes with bird diversity. However, the dominance of built spaces and man-made vegetation differed from natural landscapes. This difference will affect the composition of birds found in the urban landscape. This paper aimed to analyze bird diversity in urban landscapes and their potential for birdwatching. The research was conducted from February to April 2020 in five cities in Java (Bogor, Sukabumi, Bandung, Yogyakarta, Surabaya). Bird data were taken using the IPA method and were carried out in 85 green open spaces. Total bird species found were 75 species, with the largest number found in Bogor (66 species), followed by Surabaya (36 species), Bandung (28 species), Sukabumi (26 species), and Yogyakarta (19 species). The locations with the highest species richness in each city are Bogor Botanical Gardens (53 species), Cikundul Agrotourism Area Sukabumi (18 species), Bandung Zoological Garden (21 species), Gembira Loka Zoo (14 species), and Pakal City Forest Surabaya (20 species). Commonly seen bird species are dominated by generalist species typical of urban landscapes (e.g., Collocalia linchi, Passer montanus, and Pycnonotus aurigaster). Bird species richness has a positive correlation with the local area and habitat diversity. A total of 74 bird species are resident species that can be found throughout the year as birdwatching objects. Only one species are migrant species namely Merops philippinus.